Oralidade e slam: uma proposta contra-hegemônica de educação - Pereira, Mislene Inocêncio (2023)
The historical paths to the graphocentric society of the Western world directly affect the way of seeing and acting in the world. When it comes to education, the roots and consequences of a single vision of the world are even deeper, since the pedagogical practice is based on this vision. When considering the different ways of teaching and learning as responsible for a democratic and equitable education, it is essential to think about the cultural processes of learning, unlearning and relearning. In these principles, lies the line of thought of this research, orality and its constructions, as well as the representations of spoken poetry of slam and interschool slam are presented as other paths for diverse and democratic education. When researching the hegemonic thought of thinking and acting, it refers to the Eurocentric view of history, as a result of which it is faced with the hierarchization of cultures and knowledge, resulting in colonial pedagogy, that is, which has its bases in the colonialist formations of society . In this sense, considerations of counter-hegemonic thinking necessarily pass through decolonial thinking. The processes of construction, organization and implementation of slam on the streets and in schools are based on the strength and reach of orality, as a counter-hegemonic proposal of education and with principles of decoloniality, a practice, therefore, that goes beyond denunciation, is the composition of an education that seeks to achieve the protagonism of students as historical subjects, a dialogical proposal of teaching and learning, building and deconstructing official concepts and, through this category, placing themselves as unique in the monopoly of knowledge, science and of the curriculum. This research seeks different, decolonial and counter-hegemonic ways to expand the categories of knowledge that favor the emancipation of the student as a historical subject.